Geology and Wine 3: Terroirs of the Walla Walla Valley appellation, southeastern Washington State, USA - Meinert, Lawrence; Busacca, Alan (Geoscience Canada, 2000)
Summary Terroir of the Walla Walla Valley appellation of Washington State is influenced by the rain shadow effect and volcanic tephra of the Cascade Mouncain Range, soils derived from Quaternary glacial sediments and wind-blown loess overlying Miocene basalt, and 3) a warm, dry climate with abundant sunshine and cool nights due to high latitude (45-48°N) and elevation. Wine flavours of Walla Walla Valley varietals (including Cabernet Sauvignon, Chardonnay, Merlot, and Syrah) appear to be influenced by low humidity, long growing season (1500-1800°C degree days), soil type and drainage, drip irrigation, pruning to restrict vine vigour, trellising methods, and overall topographic climatic setting of the vineyards. Microclimates within the Walla Walla Valley appellation, combined with variations in soil and bedrock stratigraphy, yield a range of wine styles as great as many larger regions and some countries.